USE OF DEMONSTRATION METHODS IN MUSICAL LITERACY CLASSES - S. M. Askarova (Journals Park Publishing, 2024)
In this article, the visual aids of education help in learning and mastering musical knowledge, the use of visual methods in musical literacy lessons, recommendations about what kind of visual methods can be used in 3rd grade musical literacy lessons.
Keywords: Demonstration methods, visual aids, technical tools, visual aids, methods of using spectacle methods.